2(-3y-1)+(2y+7)=a

Simple and best practice solution for 2(-3y-1)+(2y+7)=a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-3y-1)+(2y+7)=a equation:


Simplifying
2(-3y + -1) + (2y + 7) = a

Reorder the terms:
2(-1 + -3y) + (2y + 7) = a
(-1 * 2 + -3y * 2) + (2y + 7) = a
(-2 + -6y) + (2y + 7) = a

Reorder the terms:
-2 + -6y + (7 + 2y) = a

Remove parenthesis around (7 + 2y)
-2 + -6y + 7 + 2y = a

Reorder the terms:
-2 + 7 + -6y + 2y = a

Combine like terms: -2 + 7 = 5
5 + -6y + 2y = a

Combine like terms: -6y + 2y = -4y
5 + -4y = a

Solving
5 + -4y = a

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -4y = -5 + a

Combine like terms: 5 + -5 = 0
0 + -4y = -5 + a
-4y = -5 + a

Divide each side by '-4'.
y = 1.25 + -0.25a

Simplifying
y = 1.25 + -0.25a

See similar equations:

| 2x+5+6x-3+30=180 | | 40.7=5b | | -3(x+9)+6x=-6 | | 3(x^3+2x^2+8x+36)=0 | | -9d-8=154 | | -0.10(13)+0.20x=0.05(x-14) | | 5(3x-6)-4=5(x-4)+76 | | 8n^2=24n+320 | | Y-8=37-7y | | 5ab+7ac-ab+3ab= | | 20x-16=20x+16 | | 4y+0.5x=12 | | 0.12y+0.06(y+3000)=720 | | -1(1+7y)-6(-7-x)=36 | | Tan(5x)=10 | | 11n-1= | | 20-16=20x+16 | | 37-2=47+5 | | 6c+4=-50 | | 7xyz+5xyz= | | logx(80)=4 | | 12x-14=10x+6 | | 7xyz+5xyz=7 | | 20x-16=20x-16 | | 0.18x+0.9(x-1)=0.1(2x-5) | | -125u^3-216v^3= | | 5w+30=8w | | 12-(x+3)=25 | | 5x+18y=180 | | (15c^2-3c)(35c-7)= | | 4+2c-3c=-9+5+c | | 4(-2)+(-7)=15 |

Equations solver categories